(untitled) (El-Wahat Journal for Research and Studies, 2025)
The Course Of This Paper Monitored The Study Approach Of Ismail Raji Al-Farouqi, And His Approach To The Subject Of Islamic Art, And The Formation Of Its Philosophy, Its Patterns And Contexts In Light Of The Monotheistic Vision, Based On The Essence Of “There Is No God But God”, And Monitored The Characteristics Of This Art And Its Philosophy Through The Artistic Process And Its Achievements From Al-Farouqi’s Perspective, And His Research From Since It Is An Art With An Independent And Unique Essence And Characteristics, It Has Its Own Reference And Goals. Its Philosophy Is Within The Scope Of Monotheism And Its Postulates, Towards The Issues Of The Universe And Existence, And The Foundations Of His Artistic Expression Of Them And His Philosophical Dealings With Them. Keywords: Philosophy; Islamic Art; The Monotheistic Vision; Ismail Raji Al-Farouqi